In vitro and in silico evaluation of monoacylglycerol lipase inhibitory activity of apigenin carbamate derivatives - Tran, The Huan; Cao, Thi Cam Nhung; Nguyen, Thanh Bich Chau; Tran, Thanh Dao (Tạp chí Y Dược Huế, 2026)
Background: Monoacylglycerol lipase (MAGL) is a key enzyme in the endocannabinoid system, involved in multiple physiological and neurological processes. Developing MAGL inhibitors from semi-synthetic flavonoid scaffolds such as apigenin carbamates offers a promising approach. Objectives: This study aimed to evaluate the MAGL inhibitory activity of semi-synthetic apigenin carbamate derivatives using integrated in vitro and in silico approaches. Materials and Methods: Four apigenin carbamate derivatives synthesized from natural apigenin were tested for MAGL inhibition using a 4-nitrophenyl acetate hydrolysis assay. Binding affinity and complex stability were investigated through molecular docking and molecular dynamics simulations. Results: Compounds A1 and A3 demonstrated improved MAGL inhibitory potency (IC50 33.04 and 40.60 µM, respectively) over apigenin, with favorable predicted binding affinities and stable interactions in the enzyme active site. Molecular dynamics simulations indicated that A1 maintained greater conformational stability, whereas A3 formed more frequent hydrogen bond interactions. Conclusion: Apigenin carbamate derivatives, particularly A1 and A3, are promising semi-synthetic leads for MAGL inhibitor development.